The Impacts of Literature on the Self-identity of Mothers of People with Disabilities: the Perception of the Subjective Self Affected by the Reading Laboratory Experience - Mituti Junior, Ricardo; Claramonte Gallian, Dante Marcello (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2022)
This article intends to demonstrate the impacts of literary narratives on women who have had their subjective self affected by virtue of filial disability. Such impacts were observed in an experience called Laboratório de Leitura, which awakens affections and promotes humanization through group debates. The study was developed from the reading and discussion of “Um Apólogo”, by Machado de Assis. The narratives produced were analyzed from a qualitative methodological approach, inspired by hermeneutic phenomenology and characterized as immersion-crystallization. The results indicate that an art-based experience can contribute to the re-elaboration of self-identities.